Missionary schools for the mari in the Krasnoufimsk uyezd, Perm province - Shilova, D.A. (Perm Federal Research Centre Journal, 2024)
The Perm Committee of the Orthodox Missionary Society, opened in 1872, set the task of educating the local non-Russian population in order to familiarize them with Russian culture as the foundation of a unified state. For this purpose, the committee began to open missionary schools throughout the Russian Empire. Such schools also appeared in Krasnoufimsk uyezd, Perm province, for the pagan Mari population. The article examines in detail the activities of nine such educational institutions in the district and attempts to assess the role of these schools in the enlightenment and education of the Mari population.